Characterization of Klebsiella pneumoniae carrying the blaNDM-1 gene in IncX3 plasmids and the rare In1765 in an IncFIB-IncHI1B plasmid - Ma, Liman; Qu, Ying; Wang, Wenji; Wang, Dongguo (Frontiers in Cellular and Infection Microbiology, 2024)
Background Today, the blaNDM gene is widely distributed on several plasmids from a variety of Gram-negative bacteria, primarily in transposons and gene cassettes within their multidrug-resistant (MDR) regions. This has led to the global dissemination of the blaNDM gene. Methods The determination of class A beta-lactamase, class B and D carbapenemases was performed according to the recommendations of the Clinical and Laboratory Standards Institute (CLSI). Antimicrobial susceptibility testing was performed using both the BioMerieux VITEK2 system and antibiotic paper diffusion methods. Plasmid transfer was then evaluated by conjugation experiments and plasmid electroporation assays. To comprehensively analyze the complete genome of K. pneumoniae strain F11 and to investigate the presence of mobile genetic elements associated with antibiotic resistance and virulence genes, Nanopore and Illumina sequencing platforms were used, and bioinformatics methods were applied to analyze the obtained data. Results Our findings revealed that K. pneumoniae strain F11 carried class A beta-lactamase and classes B+D carbapenemases, and exhibited resistance to commonly used antibiotics, particularly tigecycline and ceftazidime/avibactam, due to the presence of relevant resistance genes. Plasmid transfer assays demonstrated successful recovery of plasmids pA_F11 and pB_F11, with average conjugation frequencies of 2.91×10-4 and 1.56×10-4, respectively. However, plasmids pC_F11 and pD_F11 failed in both conjugation and electroporation experiments. The MDR region of plasmid pA_F11 contained rare In1765, TnAs2, and TnAs3 elements. The MDR2 region of plasmid pB_F11 functioned as a mobile genetic “island” and lacked the blaNDM-1 gene, serving as a “bridge” connecting the early composite structure of bleMBL and blaNDM-1 to the recent composite structure. Additionally, the MDR1 region of plasmid pB_F11 comprised In27, TnAs1, TnAs3, and Tn2; and plasmid pC_F11 harbored the recent composite structure of bleMBL and blaNDM-1 within Tn3000 which partially contained partial Tn125. Conclusion This study demonstrated that complex combinations of transposons and integron overlaps, along with the synergistic effects of different drug resistance and virulence genes, led to a lack of effective therapeutic agents for strain F11, therefore its dissemination and prevalence should be strictly controlled.